Multiwavelength electronic speckle pattern interferometry for surface shape measurement - Barbosa, Eduardo A.; Lino, Antonio C. L. (Optical Soc Amer, 2007)
Profilometry by electronic speckle pattern interferometry with multimode diode lasers is both theoretically and experimentally studied. The multiwavelength character of the laser emission provides speckled images covered with interference fringes corresponding to the surface relief in single-exposure processes. For fringe pattern evaluation, variations of the phase-stepping technique are investigated for phase mapping as a function of the number of laser modes. Expressions for two, three, and four modes in four and eight stepping are presented, and the performances of those techniques are compared in the experiments through the surface shaping of a flat bar. The surface analysis of a peach points out the possibility of applying the technique in the quality control of food production and agricultural research. (c) 2007 Optical Society of America.